2017
DOI: 10.1073/pnas.1711836114
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing catalysis in water

Abstract: Principles for designing self-healing water-splitting catalysts are presented together with a formal kinetics model to account for the key chemical steps needed for self-healing. Self-healing may be realized if the catalysts are able to self-assemble at applied potentials less than that needed for catalyst turnover. Solution pH provides a convenient handle for controlling the potential of these two processes, as demonstrated for the cobalt phosphate (CoP i ) watersplitting catalyst. For Co 2+ ion that appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
103
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 34 publications
10
103
0
2
Order By: Relevance
“…[8] However in that case no concurrent oxidation of Fe was observed and bond length changes due to Co/Feoxidation during the Co 2+/3+ oxidation wave and during the OER were not separated. Since Co is the only element present, it must be part of the active site.I ft he rate-determining step (RDS) in oxygen evolution is OÀOb ond formation, as has been reported for CoO x H y catalysts in neutral pH, [29,41,42] the edge shift could be attributed to the accumulation of nominally Co 4+ intermediates prior to the RDS.I nc ontrast, when the OER is occurring on Co(Fe)O x H y ,F e 3+ is further oxidized while Co 3+ is not. [24] Balasubramanian et al reported Fe oxidation and FeÀOb ond shortening ex situ in anodically polarized Ni(Fe)O x H y films.…”
mentioning
confidence: 77%
“…[8] However in that case no concurrent oxidation of Fe was observed and bond length changes due to Co/Feoxidation during the Co 2+/3+ oxidation wave and during the OER were not separated. Since Co is the only element present, it must be part of the active site.I ft he rate-determining step (RDS) in oxygen evolution is OÀOb ond formation, as has been reported for CoO x H y catalysts in neutral pH, [29,41,42] the edge shift could be attributed to the accumulation of nominally Co 4+ intermediates prior to the RDS.I nc ontrast, when the OER is occurring on Co(Fe)O x H y ,F e 3+ is further oxidized while Co 3+ is not. [24] Balasubramanian et al reported Fe oxidation and FeÀOb ond shortening ex situ in anodically polarized Ni(Fe)O x H y films.…”
mentioning
confidence: 77%
“…Since Co is the only element present, it must be part of the active site. If the rate‐determining step (RDS) in oxygen evolution is O−O bond formation, as has been reported for CoO x H y catalysts in neutral pH, the edge shift could be attributed to the accumulation of nominally Co 4+ intermediates prior to the RDS. In contrast, when the OER is occurring on Co(Fe)O x H y , Fe 3+ is further oxidized while Co 3+ is not.…”
Section: Figurementioning
confidence: 72%
“…The redox potential (of formation) of a catalytic species is key to the viability of the self‐healing mechanism. That is, the material must have a high enough redox potential to perform the water oxidation reaction yet a low enough redox potential that the material can reform under the water oxidation conditions . In this description of a self‐healing mechanism, the metal oxide material acts as a transient, or metastable, species which is consumed in the water oxidation reaction (2 MnO x +4 H + ⇌O 2 +2 Mn 2+ +2 H 2 O) and reformed from the solution (Mn 2+ +2 H 2 O⇌MnO x +4 H + +2 e − ).…”
Section: Discussionmentioning
confidence: 99%